Effect of Carrier Materials in Foam-Mat Drying on the Flow Properties of Kombucha Tea Powder - Martihandini, Nooryza; Handayani, Nuri (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
The high water content in kombucha tea drinks will trigger decomposition through chemical reactions and microbial contamination. The formulation of beverages into powders can reduce the water content in the preparation so as to extend the product's shelf life. Foam matt drying is one of the techniques to produce powder from kombucha tea. The choice of carrier material in the encapsulation process will affect the physical characteristics of the product. This study aims to formulate and evaluate the flow properties of kombucha powder made through the foam mat drying method with variations of maltodextrin, inulin and gom arabic carrier materials. The powder was formulated with 6 variations of carrier materials namely maltodextrin (F1), inulin (F2), gom arabic (F3), maltodextrin:inulin (1:1) (F4), maltodextrin-gom arabic (1:1) (F5) and inulin-gom arabic (1:1) (F6). The powders were evaluated for their characteristics including percent compressibility, Hausner ratio, flow velocity, angle of repose and moisture content. The results showed that F3 powder had the smallest percent compressibility and Hausner's ratio so that it had the best flow properties. The flow properties of all formulas are relatively poor due to the composition of hygroscopic carrier materials. The moisture content of kombucha powder is in the range of 0.85-3.26% with the best formula is F1.